Chemical Kinetic Study on Dual-Fuel Combustion: The Ignition Properties of n-Dodecane/Methane Mixture - Weijian Zhou; Song Zhou; Hongyuan Xi; Majed Shreka; Zhao Zhang (International Journal of Chemical Engineering)
The natural gas (NG)/diesel dual-fuel engine has attracted extensive attention in recent years, and the influence of ignition delay on the engine is very important. Therefore, the research on the ignition delay of NG/diesel dual fuel is of great significance. In this work, a simplified n-dodecane mechanism was used to study the effect of methane mixture ratio on the n-dodecane ignition process. The results showed that the ignition delay time increased with the increase of methane content by changing the mixing ratio of methane and n-dodecane. However, the effect of methane on the ignition delay time gradually decreases when the content of the n-dodecane mixing ratio is greater than 50%. It was also found that with the increase of n-dodecane content, the reduction degree of the ignition delay time of the whole reaction system decreased and the negative temperature coefficient (NTC) behavior increased. Moreover, when the initial pressure increased from 20 bar to 60 bar, the thermal effect of methane also increases from 7.03% to 9.55%. The relationship between ignition characteristics of methane-n-dodecane and temperature was studied by changing the initial temperature. Furthermore, the evolution of species in the ignition process of the whole reaction system was analyzed, and the decomposition of n-dodecane first occurs in the reaction n-C12H26 + O2 = R + HO2 to form R and free radicals; however, the reaction CH4 + OH = CH3 + H2O dominates with the increase of the methane mixing ratio and inhibits the ignition process. Through the analysis of reaction paths, sensitivity, and rates of production and consumption of methane/n-dodecane, it was explained how n-dodecane accelerates methane ignition through the rapidly formed free radicals.